Identification of maize (Zea mays) hybrids with enhanced thermotolerance using temperature induction response technique - RAJESH PALADUGU; RAMESH THATIKUNTA; KESHAVULU KUNSOTH; FARZANA JABEEN; PRAKASH BABU (Seed Research, 2026)
The experiment was conducted to identify thermotolerant single cross maize (Zea mays L.) hybrids. The freshly-harvested sun-dried seeds (below 10% moisture content) of 15 maize hybrids were used to determine optimum induction and recovery growth and were further screened for temperature tolerance. Optimum lethal and induction temperatures were assessed for seedling recovery growth (root + shoot). The optimum lethal temperature for 80% reduction in seedling growth was observed as 52°C for 2 hr. The optimum induction temperature was found to be 35°C for 1hr +40°C for 1hr + 45°C for 2hr, where maximum recovery growth was recorded after induction of hybrids to lethal temperature. Twenty one days old seedlings were assessed for dry weight and chlorophyll stability index (CSI). Based on Z-analysis, Kaveri 50, 30V 92 and RHM 25 were identified as temperature tolerant, whereas KHM218, GHM145, GK3060, and BIO9637 as temperature susceptible genotypes.